PENERAPAN STRATEGI PEMBELAJARAN INKUIRI BERBANTUAN MEDIA KOMPUTER TERHADAP KREATIVITAS BELAJAR FISIKA SISWA - Rambe, Aslamiyah (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman)
AbstractThe problem in this study is that the learning approach applied by the teacher is direct learning, student learning activities are still lacking and student physics learning outcomes are still low. This study aims to determine the differences in students physics learning creativity, and differences in student learning outcomes with the implementation of inquiry learning strategies assisted by computer media with inquiry learning strategies in class XI PLUS in Padangsidimpuan 6 Public High School. sampling. The instruments used to collect data are tests and questionnaires. As for the tests used are validated and feasible tests. Testing hypotheses using the t test, with a significance level of 5%. The results of the t-test analysis show: there are differences in student learning creativity with the implementation of inquiry learning strategies assisted by computer media by not using computer media in class XI PLUS in Padangsidimpuan 6 Public High School. This can be proven by comparing between tcount and ttable, then tcount> ttable = 3.67> 1.69 means that H0 is rejected and Ha is accepted and the results of the creativity questionnaire show that the percentage of students is 77.25% while in the control class 66.48 %. The test hypothesis also shows that by comparing between tcount and ttable, tcount> ttable = 7.25> 1.69 means that H0 is rejected and Ha is accepted, meaning that there are differences in student physics learning outcomes through the application of computer media-assisted inquiry learning strategies on fluid material Static in class XI at Padangsidimpuan 6 Public High School.Â Keywords: Inquiry Learning Strategy, Creativity, Static Fluid